Cannabinoid-based medicines in clinical care of chronic non-cancer pain: an analysis of pain mechanism and cannabinoid profile - Lucile Rapin; Maria Fernanda Arboleda; Erin Prosk; Charles Sun; Alain Watier; Michael Dworkind (Open Exploration Publishing Inc., 2023)
Aim: Among treatments for chronic non-cancer pain (CNCP), cannabinoid-based medicines (CBMs) have become extremely popular. Evidence remains modest and limited primarily to delta-9-tetrahydrocannabinol (THC) for neuropathic pain; nevertheless, the use of various CBMs, including cannabidiol (CBD) to treat neuropathic, nociceptive, and mixed pain has increased globally. This observational case-series assessed the impact of CBMs as a complementary treatment by pain mechanism and cannabinoid profile over three months. Methods: An analysis of patients with CNCP and treated with CBMs who consented to an ongoing registry was performed. Outcomes were patient-reported such as the Edmonton Symptom Assessment System-Revised, Brief Pain Inventory-Short Form, and 36-Item Short Form Health Survey. Data from patients with complete outcomes for baseline and 3-month follow-up was extracted. Characteristics of adverse drug reactions (ADRs), including a description of the suspected product were also assessed. Results: A total of 495 patients were part of this analysis (mean age = 56 years old; 67% women). At 3-month, the proportional use of THC:CBD balanced and THC-dominant products increased. Patients with neuropathic pain had higher pain-severity scores vs. nociceptive pain. In addition to patients with neuropathic pain, patients with nociceptive and mixed pain also reported improvements in pain severity and secondary symptoms such as anxiety, depression, drowsiness, fatigue, sleep disturbances, and overall, health-related quality of life. THC-dominant treatment is more likely to be recommended when pain is severe, whereas CBD-dominant is favored for less severe cases. ADRs were more frequent among cannabis-naive patients and included dizziness, headache, and somnolence among others. Conclusions: Findings suggest that CBMs can be effective for neuropathic as well as nociceptive and mixed pain. THC is more frequently recommended for neuropathic and severe pain. Future research on CBMs in pain management must include details of CBM composition, and pain mechanism and must consider potential ADRs.